LITERASI MATEMATIKA SISWA SMP DITINJAU DARI KEMAMPUAN AWAL - Nining Setyaningsih; Luthfina Nur Azizah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Mathematical literacy is a student's skill in formulating, applying, and deciphering mathematics into various situations. The main abilities as a basis in mathematical literacy are communication, mathematics, representation, reasoning and reasoning, strategies in solving problems, the use of symbols and the operation and use of mathematical tools. This study aims to describe the literacy skills of junior high school students in Pythagorean material. This research method uses descriptive qualitative. The subject of research of class VIII A students of SMP Negeri 1 Baturetno. This study used test instruments, interviews, and documentation. Data analysis techniques use pipeline methods, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study proved that the mathematical literacy ability of students with high, medium, and low initial abilities in Pythagorean material gave different results. This is shown by the ability of peny.